A review on surface modification of nanofibrous textiles for diverse applications: Focus on medical uses - Rasool Shabanloo; Majid Montazer; Ali Farahani; Nesa Karimi (Heliyon)
Electrospun nanofibers with a high surface area are attractive materials for biomedical applications. They have potential use in scaffolds, drug delivery, bio face masks, wound dressings, and biosensors. Various surface modifications have been developed to improve their chemical and physical properties. These modifications include physical, chemical, biological, and nano-treatment approaches. The physical modification includes annealing, stretching, and plasma treatment. Chemical modification includes functionalization with chemical groups, while biological modification involves coating with proteins, enzymes, or antibodies. Nanotreatment approaches use nanomaterials to modify the surface of nanofibers. These modifications enhance the characteristics of the biomedical nanofibers, making them more effective and efficient for their intended applications. The review summarizes the latest research on electrospun nanofiber modification procedures, strategies, and utilities for various biomedical applications. It provides insights into the conditions and requirements of each modification approach and their effects on the properties of the nanofibers. Moreover, it emphasizes the importance of functionalizing nanofibers to meet the most important specific requirements and the potential of electrospun nanofibers in various biomedical applications.